Gas Transportation System of Transition to "Green Technology" - Khodjaeva, C.; Akhmedov, Sh.; Karimov, A.; Musaev, M.; Abdurakhimonova, A. (European Journal of Life Safety and Stability (2660-9630), 2022)
The gas transmission system consists of a complex structure. In the Republic, the gas transportation system consists of a three-stage system, since already in the world almost many states have switched to a two- or one-stage system. The article presents data on the gas transmission system, their impact on the environment. And also the feasibility study and the transition to green technology are given.